The Figure of the Ghost: Textual and Diegetic Haunting in Chatterton, Hawksmoor and English Music by Peter Ackroyd - Lise Lefebvre ([sic], 2024)
Peter Ackroyd’s novels explore encounters with the past in the present of literary creation. Through the figure of the ghost, the usual borders between past and present are crossed as elements or characters from the past resurface in the present. This analysis explores the ways in which Ackroyd’s works engage with the past in three singular life narratives. It hovers around two main steps that highlight conversations with the past: the first one considers the textual instances of communication, while the second addresses diegetic components. Through ‘transtextuality,’ past words and texts are used again in the novels, emphasizing how the ghost of the English canon pervades and invades Ackroyd’s works. Through the apparitions of spirits, along with the introduction of all-absorbing places, objects, or bodies of communication, spectral manifestations keep resurfacing in the novels. The ghost of the English literary tradition combined with specters and spirits embody how Ackroyd’s life narratives enable conversations with the past.